Breaking down the barriers to clean air: The effects of China’s Zero-Waste City policy on PM2.5 concentration - Wei Wang (Chinese Journal of Population, Resources and Environment)
As urbanization accelerates globally, air pollution—particularly PM2.5—is becoming an increasingly significant threat, not only to public health but also the environment. In-depth research on the impact of China’s Zero-Waste City pilot policy on PM2.5 concentration offers valuable insights into the policy’s effectiveness and provides a potential model for environmental governance worldwide. This study employs panel data from 293 Chinese cities from 2014 to 2022 to systematically analyze the impact of the Zero-Waste City policy on PM2.5 concentration using a difference-in-differences model. The findings indicate that the policy not only directly reduces PM2.5 concentration but also indirectly curbs PM2.5 emissions by enhancing green innovation and green economic efficiency. Moreover, the policy’s effects are found to be positively moderated by urban energy dependence and digital financial inclusion, while they are negatively moderated by the government debt ratio. Based on these findings, this study suggests that cities should actively develop their digital economy, reduce government debt, promote green innovation, and improve green economic efficiency, as doing so will enhance their implementation of environmental policies and promote sustainable urban development.